Commercialization of academic research. A comparison between researchers in the U.S. and Finland - Tuomo Nikulainen; Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2013)
This paper aims to identify factors that relate to scientists' propensity to make commercially significant scientific discoveries (inventions) and to describe how these inventions are commercialized. Based on a large survey of academics active in different fields of science at U.S. universities, the paper benchmarks the top 20 universities against the rest, identifying the impact of different institutional settings. To highlight the institutional setting, the paper also compares these results to similar survey data from Finland, representing a small, highly educated European country. This comparison addresses the `European paradox' in university technology commercialization, which is characterized by high investments in university research and disappointingly low levels of inventions and related commercialization activity. The results show that the likelihood of making commercially valuable scientific discoveries in the U.S. is driven by motivations related to the identification of commercial opportunities and working in interdisciplinary research environments. There are also significant differences between the various fields of science. In the top U.S. universities, the funding sources for scientists more likely to make inventions are more diversified and unique. The results for Finland are surprisingly similar, suggesting that the cause of the `European paradox' seems to originate in the commercialization of inventions rather than their generation. When focusing on inventors who actively pursue commercial goals, both U.S. and Finnish inventors prefer licensing as the most popular way of taking scientific discoveries to the market. Consulting and entrepreneurship rank second and third, respectively. The countries differ with respect to both the inventors' motivations to commercialize inventions and their reasons to refrain from it. In Finland, the motivations for not pursuing commercial opportunities are much more prominent than among U.S. scientists.
Keywords: O30; O38; O33; O34; 330; academic inventions; innovation; commercialization of research; academic entrepreneurship